Name and Power Relation to African-American Identity in Ralph Ellison’s Invisible Man - Turmuzy, Imam Ahmad; Nahdhiyah, Nahdhiyah; Ahmad, Ahmad (Journal of Language and Literature, 2024)
This study aims to explore the relationship between names and African-American identity in Ralph Ellison's Invisible Man. Through a qualitative descriptive analysis, the study investigates how power relations influence the construction of African-American identity in the novel. This study used semiotic approach by applying Charles Sander Peirce’s semiotic theory in examiningg the use of name, as well as sociological approach by applying Michel Foucault's concept of power relations in analyzing power relation to social identity. The findings reveal that names, while significant, are not the sole determinants of African-American identity. The study discovers that, after the Civil War, many African-American characters in the novel chose names of European origin in an attempt to avoid negative racial stigma and discrimination. Instead, the study finds that identity construction is primarily shaped by social categorization and comparison and that power relations play a crucial role in limiting positive representations of African-American identity. This study sheds new light on the relationship between names, power, and African-American identity in literature and provides insights into the ongoing discourse surrounding these important cultural and social issues.